Diseño e implementación de un prototipo utilizando la metodología de ingeniería inversa para la construcción del módulo didáctico inversor trifásico de 1 KW - Sangucho Quispe, Byron David (2018)
Due to the demand of students in the Electronic Engineering career belonging to the Universidad Politécnica Salesiana Quito, and to the existence of a single three-phase inverter in the Electrical Machines laboratory, consequently the students do not complement the theoretical concepts about the operation of a investor and therefore practices are not performed in this laboratory. The reverse engineering method for the construction of a three-phase inverter will allow the improved design of an inverter that will serve as teaching equipment for the laboratory of electrical machines This project proposes the design and implementation of a prototype of a three-phase inverter training module of 1kW using the methodology of reverse engineering, where a process using a variety of techniques in the form of models, schemes, guidelines will be carried out. Selecting the device to test and duplicate it, making the respective improvements, in this case the device to be duplicated will be the KENTAC 3306 inverter module of Japanese origin. For the construction of the inverter a detailed study is carried out and it is determined how it works, how it is constituted electrically and electronically to determine the factors to be improved, allowing with this project to acquire elementary knowledge related to the Theory of Design and Microprocessed Systems subjects. Dictate in the career of Electronic Engineering of the Salesian Polytechnic University.